Abdominal compressions during cardiopulmonary resuscitation: a scoping review - Magda Mileyde de Sousa Lima; Maria Aline Moreira Ximenes; Dariane Veríssimo de Araújo; Lívia Moreira Barros; Nelson Miguel Galindo Neto; Joselany Áfio Caetano (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objectives: to map the scientific evidence on the use of abdominal compressions during cardiopulmonary resuscitation in patients with cardiac arrest. Methods: this is a scoping review based on the question: "What is the evidence regarding the use of abdominal compressions during cardiopulmonary resuscitation in patients with cardiac arrest?". Publications up to August 2022 were collected from eight databases. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews was used. Results: seventeen publications were included. The identified general population consisted of adults and elderly individuals. The primary outcome revealed significant rates of return of spontaneous circulation. Secondary outcomes indicated a significant improvement in heart rate, blood pressure, oxygen saturation, and other outcomes. Conclusions: abdominal compressions have been shown to be beneficial. However, further clinical studies are needed to identify the best execution method and its impacts.